The Effect of Stimulus Size and Position on the Task Performance of an Eye Mouse: Comparing Blink and Dwell Methods in a Click Task. Issue 7 (3rd July 2018) - Kim, Minjee; Jin, Daehwan; Rhiu, Ilsun; Yun, Myung Hwan
ABSTRACT: Eye mouse devices are operated by ocular movements, which have proven to be useful for disabled people who find eye control to be the easiest input method. However, there are few studies comparing the two typical click methods for eye mouse (blink and dwell) in identical experimental conditions for general object selection operations. Especially, investigation on task performance (effectiveness and efficiency) of selecting objects is not sufficient. Therefore, this study aims to investigate the relationships between task performance of selecting a stimulus and independent variables with comparing the two different click methods. To investigate the relationship, movement distance, eye input method, stimulus position, and stimulus size were considered as independent variables. Results of the blink method revealed a higher efficiency than the dwell method, particularly as the stimulus size increased. Also, both efficiency and effectiveness of stimuli in upper parts of screen was higher than for those in lower ones. Additionally, efficiency was remarkably higher when the stimulus size increased. The results of this study may be used as guidelines to design interfaces using an eye mouse device. Especially, it can be applied to various conditions of selecting an object in the working environment using the eye mouse.